Derechos humanos y la dignidad humana como presupuesto de la eutanasia - Aguilera Portales, Rafael; González Cruz, Joaquín (Pontificia Universidad Católica del Perú. Fondo Editorial, 2012)
Human rights and human dignity as assumption of euthanasiaThis article has a philosophical approach to provide us interesting thoughts in order to understand the euthanasia. To that end, initially it analyzes death connotations in the society in which we live followed by a broad reflection around death’s problem and human dignity in the capitalist society. Next, a rigorous analysis on human’s dignity idea in order to link its content with euthanasia reflection as well as with the end of life care is presented; reaching to critical conclusions of existing medical and legal regulations. Finally, some allegations and suggestions of analyzed issues are submitted.

El artículo parte de un enfoque filosófico para brindarnos interesantes reflexiones para la compresión de la eutanasia. Para ello, inicialmente analiza las connotaciones que tiene la muerte dentro de la sociedad en la que vivimos para luego presentar una reflexión amplia alrededor del problema de la muerte y la dignidad humana en la sociedad capitalista. Seguidamente, se analiza rigurosamente el concepto de dignidad humana con la finalidad de relacionar su contenido con la reflexión sobre la eutanasia y con el cuidado de la muerte, arribando a conclusiones críticas de las regulaciones médicas y legales existentes. Finalmente, se presentan algunas reflexiones y sugerencias sobre los temas analizados
Keywords: Dignidad humana; Eutanasia; Muerte; Sociedad clasista; Vida; https://purl.org/pe-repo/ocde/ford#5.05.00